Antimicrobial activity of some 2- and 3-pyridinyl-1H-benzimidazoles and their FeIII, CuII, ZnII, and AgI complexes - Tavman, A; Ulküseven, B; Birteksöz, S; Otük, G (Folia microbiologica, 2003)
2-(2-Pyridinyl)- (LI), 2-(6-methyl-2-pyridinyl)- (LII), 2-(6-methyl-2-pyridinyl)-5-methyl-(LIII), 2-(3-pyridinyl)- (LIV), 2-(3-pyridinyl)-5-methyl-1H-benzimidazoles (LV) and their complexes with Fe(NO3)3, Cu(NO3)2, Zn(NO3)2, and AgNO3 were synthesized and antibacterial activity of the compounds was tested toward Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhi, Shigella flexneri, Proteus mirabilis and antifungal activity against Candida albicans. The methyl groups of LIII increase the antimicrobial activity. The AgI complexes have considerable activity toward the microorganisms. Some ZnII complexes show an antimicrobial effect against S. aureus and S. flexneri, although the ligands themselves have no effect. CuII complexes have a considerable antibacterial effect to S. aureus and S. epidermidis.
Keywords: Microbial Sensitivity Tests; Benzimidazoles; Ligands; Metals, Heavy; Candida albicans; Bacteria; mikrobiální testy citlivosti; těžké kovy; Anti-Infective Agents; ligandy; antiinfekční látky; spektroskopie infračervená s Fourierovou transformací; Magnetic Resonance Spectroscopy; Spectroscopy, Fourier Transform Infrared; magnetická rezonanční spektroskopie; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; benzimidazoly